A self-locking steel bearing connection for circular reinforced concrete columns. Issue 12 (September 2019) - Jing, Denghu; Cao, Shuangyin; Krevaikas, Theofanis; Bian, Jun
This article proposes a new connection between a steel bearing and a reinforced concrete column, which is mainly used for provisionally providing jack support in existing reinforced concrete structures. In this suggested connection joint, the steel bearing consisted of two or four symmetrical components assembled by high-strength bolts, which surrounds the reinforced concrete column by a tapered tube and balances the vertical load via the friction force between the tapered tube and concrete, that is, through a self-locking mechanism. The proposed connection joint can be assembled easily at a construction site and can also be disassembled and reused many times. To demonstrate the feasibility of this type of connection joint, a simple test was conducted to illustrate the concept, that is, a total of four medium-scale steel bearing–reinforced concrete column connections with circular cross sections were fabricated and tested under axial loading. The test results showed that the steel bearing–reinforced concrete column connection based on self-locking mechanism exhibited good working performance. Furthermore, a simplified formula to predict the axial stiffness of the connection joint was presented. From the tests and the proposed formula, the most important factors that influence the axial stiffness of this type of connection joint on the premise of an elastic working state are the slope of the tapered tube, the height of the steel bearing, the thickness of the tapered tube, the cross section of the reinforced concrete column, the cross-sectional area of all the connecting bolts, the proportion of the number of top bolts, the area of the top ring plate, and the effective contact area ratio.